PENGARUH KONVERGENSI IFRS DAN MEKANISME CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Audita Ananda Nundini; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2014)
This study aimed to determine the effect of IFRS convergence and corporate governance mechanisms which were proxied by proportion of independent commissioner, managerial ownership, and institutional ownership to earning management. The independent variable in this study are IFRS convergence, proportion of independent commissioner, managerial ownership, and institutional ownership. The dependent variable is earning management. The sample was a manufacturing companies listed in Bursa Efek Indonesia (BEI)  that conducted in 2010-2011 as many 102 companies with a sampling technique is using purposive sampling method. The statistical tool test for hypothesis testing is SPSS 20. The result showed that the IFRS convergence and the proportion of commissioner independent don’t influence on earning management. The managerial ownership has a significant negative effect on earning management and the institutional ownership has a positive effect on earning management.